TAFSIR EKOLOGI - Mamluatun Nafisah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
This paper wants to position environmental aspects as the main doctrine (ushūl) of Islamic law which is possible to influence and change the mainstream of human beings to behave well towards the existence of the environment. Ontologically, the hifẓ al-bī'ah paradigm is built on the basis of the maṣlaḥah concept which is the core of the concept of maqāṣid ash-sharī'ah formulated in al-kulliyyāt al-khamsa (Five basic benefits), namely guarding religion (hifẓ ad-din) , guarding the soul (hifẓ an-nafs), guarding offspring (hifẓ an-nasl), guarding reason (hifẓ al-'aql) and safeguarding wealth (hif (al-māl). These five things are a necessity to enforce benefit. Specifically the correlation of al-kulliyyāt al-khamsa related to environmental conservation, are: First, Environment is a key word in building a religious society order. Why not, belief in the creator must begin with an introduction to the universe. Second, the environment is the basis of survival. Third, there is an appropriate punishment for perpetrators of environmental damage.